PRAgmatic Clinical Trial Design of Integrative MediCinE (PRACTICE): A Focus Group Series and Systematic Review on Trials of Diabetes and Kidney Disease - Chan, Kam Wa; Lee, Pak Wing; Leung, Crystal Pui-sha; Law, Yee Kwan; Gao, Lucy; Chan, Gary Chi-wang; Yiu, Wai Han; Lam, Tai Pong; Tang, Sydney Chi-wai (Frontiers in Medicine, 2021)
Background Pragmatic trials inform clinical decision with better generalizability and bridge different streams of medicine. This study collated the expectations regarding pragmatic trial design of integrative medicine (IM) for diabetes and kidney diseases among patients and physicians. Dissonance between users’ perspective and existing pragmatic trial design was identified. Method A 10-group semi-structured focus group interview series (21 patients, 14 conventional medicine (ConM) and 15 Chinese medicine (CM) physicians) were purposively sampled from private and public clinics in Hong Kong. Perspectives were qualitatively analysed by constant comparative method. A systematic search of 4 databases was performed to identify existing IM pragmatic clinical trials in diabetes or kidney disease. Primary outcomes were the pragmatism, risk of bias and rationale of study design. Risk of bias and pragmatism was assessed based on Cochrane risk-of-bias tool and PRECIS-2, respectively. Correlation between risk of bias and pragmatism was assessed by regression models with sensitivity analyses. Results Subtheme on the motivation to seek IM service was analysed, covering perceived limitation of ConM effect, perceived benefits of IM service and assessment of IM effectiveness. Patients expected IM service to retard disease progression, stabilize concomitant drug dosage and reduce potential side effects associated with ConM. In the systematic review, 25 studies from 6 countries were included covering CM, Korean medicine, Ayurvedic and western herbal medicine. Existing study designs did not include detailed assessment of concomitant drug change and adverse events. Majority of studies either recruited a non-representative proportion of patients as traditional, complementary and integrative medicine (TCIM) diagnosis was used as inclusion criteria, or completely dropped TCIM diagnosis in the trial design. Consultation follow-up frequency is the least pragmatic domain. Increase in pragmatism did not associate with a higher risk of bias. Conclusion Existing IM pragmatic trial design does not match the patients’ expectation in the analysis of incident concomitant drug change and adverse events. A two-layer design incorporating TCIM diagnosis as a stratification factor maximizes the generalizability of evidence and real-world translation of both ConM and TCIM.